Pengaruh Program Stimulasi Literasi Terhadap Aktivitas Literasi dan Kemampuan Literasi Awal Pada Anak Prasekolah - Hapsari, Widyaning (2016)
Literacy stimulation program is a form of treatment by providing literacy packages containing guidebooks literacy activities and a set of media literacy in children and socialization for mothers. The purpose of this study was to test the effectiveness of the stimulation program to improve literacy activities and literacy skills in preschoolers. The method used in this study is a quasi experimental design with non-equivalent control group. Subjects were 30 children aged 3-5 years who were divided into an experimental group and a control group. The experimental group numbering 15 children given the treatment in the form of stimulation literacy program. Packages containing literacy literacy activities guide books, activity books preschoolers, children's story books, dolls, tools of educational games, and other media literacy. While socialization is given to the mother at the beginning of the program as an explanation of the content of the program and the role that can be given the mother during the program. Based on the analysis by the non-parametric statistical test Mann-Whitney U, it is known that there are differences increased activity and early literacy skills in the experimental group and control group. Qualitative analysis also supports this, namely that the intention and the quality of child literacy activities increased after being given a literacy package. Meanwhile, the increase in literacy seen by observing the change in the measurement results.